The last resort: reducing avoidable employee harm by improving the application of the disciplinary policy and process - Cooper, Andrew; Teoh, Kevin Rui-Han; Madine, Ruth; Neal, Adrian; Jones, Aled; Hussain, Ammarah; Behrens, Doris A. (Frontiers in Psychology, 2024)
Introduction There is growing evidence within the healthcare sector that employee investigations can harm individuals involved in the process, an organization’s culture and the delivery of its services. Methods This paper details an intervention developed by an NHS Wales organization to reduce the number of its employee investigations through an organization-wide focus that promoted a ‘last resort’ approach and introduced the concept of ‘avoidable employee harm’. A range of associated improvement initiatives were developed to support behavior change among those responsible for determining whether an employee investigation should be initiated. Results Over a 13-month period, organizational records showed an annual reduction of 71% in investigation cases post-intervention, resulting in an estimated 3,308 sickness days averted annually and total estimated annual savings of £738,133 (based on direct savings and costs averted). This indicates that the organization has started to embrace the “last resort” approach to using employee investigations to address work place issues. The programme was supported with training for those responsible for commissioning and leading the organization’s employee investigations. Analysis of survey data from those who attended training workshops to support the programme indicated that participants showed an increased awareness of the employee investigation process post-workshop and an understanding of the concept of avoidable employee harm. Discussion The programme is congruent with the Healthy Healthcare concept, as the study illustrates how its practices and processes have a beneficial impact on staff, as well as potentially on patients. This study highlights wider issues for consideration, including the: (1) the role of Human Resources (HR), (2) taking a multi-disciplinary approach, (3) culture and practice, (4) the responsibility of the wider HR profession.